(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Testosterone is an androgen, which is a “male” sex hormone that plays a role in reproduction, growth, and maintenance of a healthy body. In men, testosterone is mainly produced in the testes. In women’s bodies, testosterone is produced in the ovaries, adrenal glands, fat cells, and skin cells. Generally, women’s bodies make about 1/10th to 1/20th of the amount of testosterone as men’s bodies.